A Dictionary of Film Studies - Kuhn, Annette; Westwell, Guy (Oxford Oxford University Press, 2012)
This authoritative dictionary features more than 500 detailed entries covering all aspects of film studies, including terms, concepts, debates, and movements in film theory and criticism, national, international and transnational cinemas, film history, film movements and genres, film industry organizations and practices, and key technical terms and concepts. Most entries also feature recommendations for further reading and a large number have web links which are regularly updated on a companion website. The dictionary is international in its approach, covering national cinemas, genres, and film movements from around the world. The most up-to-date dictionary of its kind available, this is a must-have for all students of film studies.
Keywords: Motion pictures